Risks Due to Pandemic and Legal Protection for Customers - Utomo, Indra Haryoko (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
The occurrence of a pandemic at the beginning of 2019 until now has had a very large loss impact, almost all over the world experiencing an economic decline, even high inflation. This condition is a blow, which requires all parties to be able to find their own way out. In the banking world, the impact of the pandemic has caused instability in interest rates and business liquidity, causing public panic, both as debtors and creditors. Therefore, this research was conducted to reveal the impact of the pandemic on the banking world in Indonesia and seek legal protection as a solution for customers. To answer the research phenomenon, a scientific method was established, namely the qualitative method. The object of research is the National Bank of Indonesia with primary and secondary data sources. Primary data was obtained through interviews, while secondary data was obtained by reviewing banking law literature. The results of the study revealed that the occurrence of the pandemic did not dampen the bank to continue to guarantee the rights of its customers. Although on the other hand, the impact of the pandemic is very significant for the banking industry, this is clearly seen in the declining number of banking activities.